„Sérénité” Aliny Skiby jako adaptacja opowiadań Jarosława Iwaszkiewicza - Gołos-Dąbrowska, Katarzyna (Załącznik Kulturoznawczy, 2024)
The article presents an analysis of Alina Skiba’s 1988 film Sérénité as a screen adaptation of Jaroslaw Iwaszkiewicz’s short stories (Dreams and Sérénité) The director’s film version is a kind of poly-adaptation – a media transformation of more than one literary work into a new authorial text. The article reveals Skiba’s adaptation strategy. The director does not so much as create a film that is close to the pretexts, but realizes in it numerous Iwaszkiewicz’s tropes and literary motifs. In doing so, she creates a completely autonomous work reflecting the atmosphere of serene reconciliation with old age present in Iwaszkiewicz’s last volume of short stories.